Judicialization of Environmental Policy and the Crisis of Democratic Accountability. Issue 1 (30th November 2016) - Kramarz, Teresa; Cosolo, David; Rossi, Alejandro
Abstract: A growing global trend of judicializing environmental policy has been received with optimism, and in the context of democracies in transition, many have found in an active Supreme Court a potential solution to political impasses. However, as the judiciary is the least democratic of the three branches of government, what impact does judicialization have on democratic accountability? We claim that judicialization generates accountability losses in two ways. First, theoretically, when the Court takes on managerial functions that extend beyond its adjudicative role, it distorts its horizontal accountability functions. Second, empirically, when the Court becomes involved in policy formulation, effectiveness is not guaranteed yet there are no vertical accountability sanctions the polity can impose on judges. We illustrate this argument with an emblematic and instructive case of judicialization of environmental policy in Argentina. We conclude that judicialization to remedy policy failures undermines democratic accountability.